Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ñ Ð½Ð° Ñ„ÑƒÐ½ÐºÑ†Ð¸Ð¾Ð½Ð°Ð»ÑŒÐ½Ñ‹Ðµ ÑÐ²Ð¾Ð¹ÑÑ‚Ð²Ð° ÑÐ´Ñ€Ð¾ÑÐ¾Ð´ÐµÑ€Ð¶Ð°Ñ‰Ð¸Ñ… ÐºÐ»ÐµÑ‚Ð¾Ðº Ð»ÐµÐ¹ÐºÐ¾ÐºÐ¾Ð½Ñ†ÐµÐ½Ñ‚Ñ€Ð°Ñ‚Ð° ÐºÐ¾Ñ€Ð´Ð¾Ð²Ð¾Ð¹ ÐºÑ€Ð¾Ð²Ð¸ Ñ‡ÐµÐ»Ð¾Ð²ÐµÐºÐ° - Goltsev, A. N.; Volina, V. V.; Ostankov, M. V.; Goltsev, K. A.; Sokol, L. V.; Brovko, Ye. V.; Chernyshenko, L. G.; Kozhina, O. Yu. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2010)
Cryopreservation effect on functional properties of more differentiated hemopoietic precursors of mature cells in human cord blood was investigated, as well as correlation between phenotypic marker expression and functional condition of these cells was assessed. Correlation between functional state of hemopoietic cells and phenotypic marker expression was noted. Maintenance of functional properties of human cord blood leukoconcentrate components was proved when the suggested method for its obtainment and cryopreservation being applied.